2022
DOI: 10.3390/nu14214490
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Modulation in Patients with Metabolic Syndrome

Abstract: Metabolic syndrome (MS) comprises a vast range of metabolic dysfunctions, which can be associated to cardiovascular disease risk factors. MS is reaching pandemic levels worldwide and it currently affects around 25% in the adult population of developed countries. The definition states for the diagnosis of MS may be clear, but it is also relevant to interpret the patient data and realize whether similar criteria were used by different clinicians. The different criteria explain, at least in part, the controversie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…The authors found that the intake of specific foods or food groups, such as whole grains, vegetables, and red meats, among others, was associated with changes in the abundance of specific genera and species of gut microbiota. Moreover, the review by Araujo, Borges-Canha, and Pimentel-Nunes [ 16 ] explored differences in the gut microbiome among individuals with metabolic syndrome (versus healthy adults) as well as the potential for probiotics and/or synbiotics to modulate the microbiome in an effort to mitigate some of the metabolic disturbances in some individuals with metabolic syndromes.…”
mentioning
confidence: 99%
“…The authors found that the intake of specific foods or food groups, such as whole grains, vegetables, and red meats, among others, was associated with changes in the abundance of specific genera and species of gut microbiota. Moreover, the review by Araujo, Borges-Canha, and Pimentel-Nunes [ 16 ] explored differences in the gut microbiome among individuals with metabolic syndrome (versus healthy adults) as well as the potential for probiotics and/or synbiotics to modulate the microbiome in an effort to mitigate some of the metabolic disturbances in some individuals with metabolic syndromes.…”
mentioning
confidence: 99%
“…For instance, direct effects may be produced by environmental pollutants or dietary components on the growth and metabolism of microorganisms leading to changes in compositional traits and activity of microbiota. [4] 1. Immune System Modulation: The host immune system helps in the development of an active microbiota and also guides the composition and functions of different structures.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…For instance, a newly introduced phototrophic microbial species in the eco-system of the microbiota through probiotics or phage therapy might lead to ecological changes that affect other community members. [4] 3. Host-Microbe Crosstalk: The messages circulating along various signaling pathways enable two-way communication between the host and its associated microbiota.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Gut microbiota regulates local and systemic functions, interfering with digestive, immune, and metabolic effects via the secretion of gut microbiota-derived components. The disturbances of gut microbiota composition, known as dysbiosis, can alter the release of microbial products that activate metabolic pathophysiological processes, defining a gut metabolism hypothesis: dysbiosis and microbial metabolites are involved in metabolic disorders, such as diabetes mellitus and dyslipidemia, through both a direct metabolic effect and the enhancement of pro-inflammatory signaling pathways [ 52 ]. Moreover, the interaction between the host genome, microbial metagenome, and diet correlates with cardiometabolic risk factors and influences the development of atherosclerotic cardiovascular diseases.…”
Section: Gut Peptides: the Mechanisms Behind The Moleculesmentioning
confidence: 99%